Customs services and ways to improve their quality in the context of digitalisation - I. Yu. Sofiyannikova (Вестник университета)
This article is devoted to problems of the process of rendering services in the field of customs during digitalisation of the economy. The observed mechanism of rendering state customs services, as well as improving their quality, naturally affect the entire service sector and the development of the country’s economy as a whole. The main purposes of the article are to analyse the mechanism of rendering services in the field of customs and to search for effective methods of assessing their quality. The relevance of the article is determined by the need to improve the operations performed to be able to manage the quality of provided customs services. The main objective of this article is to propose possible ways to reduce time costs without losing the quality of customs control in the process of providing the services. The article used both theoretical (analysis of the current legislation) and empirical research methods (giving practical examples of improving the efficiency of customs operations and the quality of customs services). The results of the study are the following: development of sequential operations performed by customs authorities in the process of rendering services in the field of customs; proposal of possible criteria for assessing their quality; formulation of options for managing this quality.